AIE Triggers the Circularly Polarized Luminescence of Atomically Precise Enantiomeric Copper(I) Alkynyl Clusters. (18th September 2019) - Zhang, Miao‐Miao; Dong, Xi‐Yan; Wang, Zhao‐Yang; Li, Hai‐Yang; Li, Shi‐Jun; Zhao, Xueli; Zang, Shuang‐Quan
Abstract: Atomically precise enantiomeric metal clusters are scarce, and copper(I) alkynyl clusters with intense circularly polarized luminescence (CPL) responses have not been reported. A pair of chiral alkynyl ligands, (R/S)‐2‐diphenyl‐2‐hydroxylmethylpyrrolidine‐1‐propyne (abbreviated as R/S‐DPM ) we successfully prepared and single crystals were characterized of optically pure enantiomeric pair of atomically‐precise copper(I) clusters, [Cu14 (R/S‐DPM)8 ](PF6 )6 (denoted as R/S‐Cu14 ), which feature bright red luminescence and CPL with a high luminescence anisotropy factor ( g lum ). A dilute solution containing R/S‐Cu14 was nonluminescent and CPL inactive at room temperature. Crystallization‐ and aggregation‐induced emission (CIE and AIE, respectively) contribute to the triggering of the CPL of R/S‐Cu14 in the crystalline and aggregated states. Their AIE behavior and good biocompatibility indicated applications of these copper(I) clusters in cell imaging in HeLa and NG108‐15 cells. Abstract : Atomar präzise chirale Cu I ‐Alkinyl‐Nanocluster R/S‐CU14 mit inhärenter Chiralität wurden erstmals synthetisiert. Kristallisations‐ und aggregationsinduzierte Emission (CIE bzw. AIE) lösen eine zirkularpolarisierte Lumineszenz (CPL) mit beispiellosem Lumineszenz‐Anisotropiefaktor ( g lum ) aus.